(untitled) (International Seven Journal of Multidisciplinary, 2023)
The integration of automation with architecture is increasingly present in entrepreneurial and commercial environments. The search for practicality, cost savings and efficiency made technologies an essential asset in these scenarios. The presence of devices involving automation is increasingly frequent in our daily lives, especially in concepts of smart homes, automated industrial production and global agriculture. Commercial architecture follows this constant evolution, offering intelligent systems that help reduce energy consumption, control climate control, provide automated lighting, refined security systems and facilitated access control, among other methods of automation in the commercial aspect. In the current scenario, the concept of shared work Coworking is a great business alternative, collaborating with the development of new professionals and boosting the growth of entrepreneurs and freelancers from the same region. These buildings provide features such as climate controls, lighting, outdoor seating, safe and easy access to the building, and reservation capabilities for meeting rooms, workspaces, and the dining area. The development of this work is based on the execution of the electrical design of a 04-story building, containing the electrical, automation and communication design of most of the enclosures, taking into account the relevant technical standards.